A Population-Based Twin Study of Childhood Irritability and Internalizing Syndromes. Issue 4 (3rd July 2020) - Rappaport, Lance M.; Carney, Dever M.; Brotman, Melissa A.; Leibenluft, Ellen; Pine, Daniel S.; Roberson-Nay, Roxann; Hettema, John M.
Abstract : Childhood irritability exhibits significant theoretical and empirical associations with depression and anxiety syndromes. The current study used the twin design to parse genetic and environmental contributions to these relationships. Children ages 9–14 from 374 twin pairs were assessed for irritability and symptoms of depression, generalized anxiety, panic, social phobia, and separation anxiety using dimensional self-report instruments. Multivariate structural equation modeling decomposed the correlations between these syndromes into genetic and environmental components to examine shared and specific risk domains. Irritability had significant associations with each internalizing symptom domain. Genetic contributions to irritability are moderately correlated with genetic risk for symptoms of depression, generalized anxiety, and separation anxiety with weaker overlap with the other anxiety syndromes. Familial and specific environmental risk factors explained covariation among syndromes and indicated potential syndrome-specific risk. There is substantial overlap among the genetic and environmental factors that influence individual differences in irritability and those that increase liability for depression and anxiety symptoms in children. These findings deepen the current understanding of childhood internalizing risk factors and provide important implications for syndrome prediction and susceptibility gene discovery efforts.